Temperature-dependent electrical transport properties in graphene/Pb(Zr0.4Ti0.6)O3 field effect transistors. (November 2015) - Zhang, Xiao-Wen; Xie, Dan; Xu, Jian-Long; Zhang, Cheng; Sun, Yi-Lin; Zhao, Yuan-Fan; Li, Xian; Li, Xin-Ming; Zhu, Hong-Wei; Chen, Hua-Mao; Chang, Ting-Chang
Abstract: We report the temperature and gate voltage dependent electrical properties of PZT gated graphene field effect transistors (PZT-GFETs) in the vacuum atmosphere. The PZT-GFETs exhibit p-type characteristics which are attributed to the chemical doping induced the Fermi level shifting below the Dirac point. Meanwhile, it also shows a large memory window. The temperature dependencies of the source-drain current in the range of 20–300 K indicate thermally activated hysteresis behaviors. The hysteresis in the transfer characteristics of PZT-GFETs shows a simultaneous enlargement with increasing temperature. The hysteresis appears to stem from the screening of charges that are transferred from graphene to traps at the interface of PZT and graphene. The magnitude of the charge neutrality point under opposite gate voltage sweep are enhanced with the increase of temperature and gate voltage can be ascribed to the common effects of the temperature and voltage magnitude dependent mechanisms such as interface charge trapping process and the polarization effects of PZT films.